2021
DOI: 10.1080/15563650.2021.1906888
|View full text |Cite
|
Sign up to set email alerts
|

Sodium azide poisoning: a narrative review

Abstract: Context: Sodium azide is a highly toxic chemical. Its production has increased dramatically over the last 30 years due to its widespread use in vehicular airbags, and it is available for purchase online. Thus, accidental exposure to azide or use as a homicidal or suicidal agent could be on the rise, and secondary exposure to medical personnel can occur. No antidote exists for azide poisoning. We conducted a systematic review of azide poisoning to assess recent poisoning reports, exposure scenarios, clinical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 43 publications
(93 reference statements)
0
32
0
Order By: Relevance
“…Health care workers are at risk of secondary exposure during treatment of intoxicated patients, especially when performing gastric lavage. However, current available literature showed no increased mortality after secondary exposure, as demonstrated by Tat et al 28 Although the majority of exposed personnel did not have any complaints, one had immediate clinical features (dizziness, dyspnea, headache, fatigue and ocular irritation) after exposure. 29 In another case, two health care workers required time off due to stress and fatigue.…”
Section: Gastric Lavage and Activated Charcoalmentioning
confidence: 74%
See 1 more Smart Citation
“…Health care workers are at risk of secondary exposure during treatment of intoxicated patients, especially when performing gastric lavage. However, current available literature showed no increased mortality after secondary exposure, as demonstrated by Tat et al 28 Although the majority of exposed personnel did not have any complaints, one had immediate clinical features (dizziness, dyspnea, headache, fatigue and ocular irritation) after exposure. 29 In another case, two health care workers required time off due to stress and fatigue.…”
Section: Gastric Lavage and Activated Charcoalmentioning
confidence: 74%
“…Rapid degradation and a time-consuming process make it even more challenging to quantify the amount of sodium azide and therefore is of no help in the treatment of a patient with a suspected intoxication with sodium azide. 4 A recently published review by Tat et al 28 only recommend the use of hydroxycobolamin as a potential treatment option. However, based on the available literature as described above, limited effects can be expected.…”
Section: Analytical Challengesmentioning
confidence: 99%
“…33 NaN 3 is a highly toxic compound, and exposure to NaN 3 poses a risk of death. 12 Researchers have proven that a high dose of NaN 3 can potentially cause the toxic damage to numerous tissues and organs. 34 This study also found that exposure to NaN 3 (17 mg/kg/day) can cause cardiac cell disarrangement, necrosis, and shrinkage of islets of Langerhans after H&E staining of heart and pancreatic tissues, respectively (Figures 8 and 9).…”
Section: ■ Discussionmentioning
confidence: 99%
“…(B) Correlation between the Co-N ax bond length and the pK base-off of cobalamins with various b-ligands owing to the trans-effect (De March et al, 2012March et al, ). et al, 2020 and azide (Tat et al, 2021) poisoning. Aquacobalamin forms a complex with isoniazid (isonicotinic acid hydrazide) (Tumakov et al, 2017), which is one of the most effective antituberculosis drugs.…”
Section: Structure Of Cobalaminsmentioning
confidence: 99%
“…have shown that cobinamide was significantly more efficacious than hydroxocobalamin when compared at equal mg/kg dosages ( Bebarta et al., 2017 ). Hydroxocobalamin or/and cobinamide are also the rational choices for treating methyl mercaptan ( Hendry-Hofer et al., 2020 ) and azide ( Tat et al., 2021 ) poisoning. Aquacobalamin forms a complex with isoniazid (isonicotinic acid hydrazide) ( Tumakov et al., 2017 ), which is one of the most effective antituberculosis drugs.…”
Section: Biochemical Characterization Of the Mmachc Proteinmentioning
confidence: 99%